Developing a democratic progress model based on discrete event systems - Park, Seong Jin; Yang, Jung Min (International Journal of Control, 2021)
In this paper, we model and analyze democratic progress and regression in the framework of discrete event systems. Since democratic progress strongly correlates with the growing number of people who meet their economic interests and political rights, it can be represented as an event-driven dynamical system evolved by local agents that make a decision to enable or disable the progress and regression events according to their private objectives. The final decision on enabling/disabling an event is made by the majority rule, which also complies with the feature of democracy. Based on majority-based supervisory control, we investigate the conditions for the democratic progress model to be progressive or regressive under full observation. Moreover, we present a scheme that can modify the characteristics of the model by designing masks for agents, i.e. the regressive system under full observation is changed to a progressive one under partial observation via masks, and vice versa.
Keywords: automaton; democratic progress; Economic interests; Final decision; Model-based OPC; Number of peoples; Partial observation; Supervisory control; automaton; democratic progress; Discrete event systems; supervisory control